2012
DOI: 10.1007/s00787-012-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adolescents mental health and use of alcohol and tobacco: a 10-year time-trend study of Finnish adolescents

Abstract: The present study examines the 10-year time-trend changes of adolescent psychiatric symptoms, smoking and alcohol use. Representative population-based samples with same methods at two time-points, same age range and with 10-year period between the time points were gathered in Finland to investigate secular changes in adolescents' emotional and behavioral problems. Seventh and ninth grade students filled in the Strengths and Difficulties Questionnaire (SDQ) and questions regarding alcohol use and smoking anonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 21 publications
4
53
0
2
Order By: Relevance
“…One plausible explanation is that this generation of youth is more affected than earlier generations. There is contradictory evidence in the international literature regarding whether younger cohorts are more affected than earlier generations [1,[27][28][29]. Even if true, it is not likely to explain the full magnitude of these differences.…”
Section: Incidence Of Mental Disordersmentioning
confidence: 93%
“…One plausible explanation is that this generation of youth is more affected than earlier generations. There is contradictory evidence in the international literature regarding whether younger cohorts are more affected than earlier generations [1,[27][28][29]. Even if true, it is not likely to explain the full magnitude of these differences.…”
Section: Incidence Of Mental Disordersmentioning
confidence: 93%
“…Since the early 1990s, alcohol use has increased considerably in most developed countries (Bauman & Phongsavan, 1999). Many countries also noted a decreasing trend in adolescent alcohol use since the beginning of the 21st century (EMCDDA & ESPAD, 2016;Kristjansson et al, 2010;Lai & Habicht, 2011;Livingston, 2014;Norström & Svensson, 2014;Sigfúsdóttir et al, 2008;Sourander et al, 2012;, although the size of the decline in the Netherlands appears to be one of the most dramatic ones. Thus, explanations for the observed trends in the Netherlands are likely to include both factors specific to the Dutch context and factors that are more internationally applicable.…”
Section: Societal Explanations For the Trendsmentioning
confidence: 99%
“…A promising development is the declining trend in adolescent alcohol use since the beginning of the 21st century that has been reported in many countries, including Australia (Livingston, 2014), Estonia (Lai & Habicht, 2011), Finland (Sourander et al, 2012), Iceland (Sigfúsdóttir, Kristjansson,Thorlindsson, & Allegrante, 2008), and Sweden (Norström & Svensson, 2014). To date, systematic trend analyses of adolescent alcohol use in the Netherlands have been lacking from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies reported slightly decreased population levels of behavioral problems [35] or both (slightly) decreased emotional and behavioral population levels [2,23] over time. Furthermore, some time-trend studies found stable population levels of emotional and behavioral problems [31,40,41]. Although the former might roughly suggest that levels of emotional problems have increased during the last decades whereas this may not be the case for behavioral problems the findings of previous research are somewhat inconsistent.…”
Section: Introductionmentioning
confidence: 97%